Respuesta :
Answer:
Tthe distance between [tex]\left(x_1,\:y_1\right)=\left(0,\:13\right)[/tex] and [tex]\left(x_2,\:y_2\right)=\left(4,\:9\right)[/tex] will be:
- [tex]\mathrm{Distance\:between\:}\left(0,\:13\right)\mathrm{\:and\:}\left(4,\:9\right):\quad 4\sqrt{2}[/tex]
Step-by-step explanation:
Given the points
- [tex]\left(x_1,\:y_1\right)=\left(0,\:13\right)[/tex]
- [tex]\left(x_2,\:y_2\right)=\left(4,\:9\right)[/tex]
[tex]\mathrm{Compute\:the\:distance\:between\:}\left(x_1,\:y_1\right),\:\left(x_2,\:y_2\right):\quad \sqrt{\left(x_2-x_1\right)^2+\left(y_2-y_1\right)^2}[/tex]
[tex]\mathrm{The\:distance\:between\:}\left(0,\:13\right)\mathrm{\:and\:}\left(4,\:9\right)\mathrm{\:is\:}[/tex]
[tex]=\sqrt{\left(4-0\right)^2+\left(9-13\right)^2}[/tex]
[tex]=\sqrt{4^2+4^2}[/tex]
[tex]=\sqrt{4^2\cdot \:2}[/tex]
[tex]\mathrm{Apply\:radical\:rule\:}\sqrt[n]{ab}=\sqrt[n]{a}\sqrt[n]{b},\:\quad \mathrm{\:assuming\:}a\ge 0,\:b\ge 0[/tex]
[tex]=\sqrt{2}\sqrt{4^2}[/tex]
[tex]\mathrm{Apply\:radical\:rule\:}\sqrt[n]{a^n}=a,\:\quad \mathrm{\:assuming\:}a\ge 0[/tex]
[tex]=4\sqrt{2}[/tex]
Therefore, the distance between [tex]\left(x_1,\:y_1\right)=\left(0,\:13\right)[/tex] and [tex]\left(x_2,\:y_2\right)=\left(4,\:9\right)[/tex] will be:
- [tex]\mathrm{Distance\:between\:}\left(0,\:13\right)\mathrm{\:and\:}\left(4,\:9\right):\quad 4\sqrt{2}[/tex]